Agricultural abandonment and re-cultivation during and after the Chechen Wars in the northern Caucasus. (March 2019) - Yin, He; Butsic, Van; Buchner, Johanna; Kuemmerle, Tobias; Prishchepov, Alexander V.; Baumann, Matthias; Bragina, Eugenia V.; Sayadyan, Hovik; Radeloff, Volker C.
Highlights: We modeled agricultural land-use change during and after the Chechen Wars. Agricultural lands closer to conflicts were more prone to be abandoned. Conflict intensity was overall positively correlated with agriculture abandonment. Limited re-cultivation of abandoned agriculture in areas closer to the conflicts. Abstract: Armed conflicts are globally widespread and can strongly influence societies and the environment. However, where and how armed conﬂicts affect agricultural land-use is not well-understood. The Caucasus is a multi-ethnic region that experienced several conflicts shortly after the collapse of the Soviet Union, most notably the two Chechen Wars, raising the question how agricultural lands were changed. Here, we investigated how the distance to conflicts and conflict intensity, measured as the number of conflicts and the number of casualties, affected agricultural land abandonment and subsequent re-cultivation, by combining social, environmental and economic variables with remotely-sensed maps of agricultural change. We applied logistic and panel regression analyses for both the First Chechen War (1994–1996) and the Second Chechen War (1999–2009) and interacted conflict distance with conflict intensity measures. We found that agricultural lands closer to conflicts were more likely to be abandoned and less likely to be re-cultivated, with stronger effects for the First Chechen War. Conflict intensity was positively correlated with agricultural land abandonment, but the effects differed based on distance to conflicts and the intensity measure. We found little re-cultivation after the wars, despite abundant subsidies, indicating the potentially long-lasting effects of armed conflicts on land-use. Overall, we found a clear relationship between the Chechen Wars and agricultural land abandonment and re-cultivation, illustrating the strong effects of armed conflicts on agriculture.